The zebrafish gene map defines ancestral vertebrate chromosomes - Woods, Ian G.; Wilson, Catherine; Friedlander, Brian; Chang, Patricia; Reyes, Daengnoy K.; Nix, Rebecca; Kelly, Peter D.; Chu, Felicia; Postlethwait, John H.; Talbot, William S.

(untitled) (Genome Research, 2005)
Genetic screens in zebrafish (Danio rerio) have identified mutations that define the roles of hundreds of essential vertebrate genes. Genetic maps can link mutant phenotype with gene sequence by providing candidate genes for mutations and polymorphic genetic markers useful in positional cloning projects. Here we report a zebrafish genetic map comprising 4073 polymorphic markers, with more than twice the number of coding sequences localized in previously reported zebrafish genetic maps. We use this map in comparative studies to identify numerous regions of synteny conserved among the genomes of zebrafish, Tetraodon, and human. In addition, we use our map to analyze gene duplication in the zebrafish and Tetraodon genomes. Current evidence suggests that a whole-genome duplication occurred in the teleost lineage after it split from the tetrapod lineage, and that only a subset of the duplicates have been retained in modern teleost genomes. It has been proposed that differential retention of duplicate genes may have facilitated the isolation of nascent species formed during the vast radiation of teleosts. We find that different duplicated genes have been retained in zebrafish and Tetraodon, although similar numbers of duplicates remain in both genomes. Finally, we use comparative mapping data to address the proposal that the common ancestor of vertebrates had a genome consisting of 12 chromosomes. In a three-way comparison between the genomes of zebrafish, Tetraodon, and human, our analysis delineates the gene content for 11 of these 12 proposed ancestral chromosomes.